2015
DOI: 10.1155/2015/590851
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers in Refractory Congestive Heart Failure Patients Treated with Peritoneal Dialysis

Abstract: Proinflammatory cytokines play a pathogenic role in congestive heart failure. In this study, the effect of peritoneal dialysis treatment on inflammatory cytokines levels in refractory congestive heart failure patients was investigated. During the treatment, the patients reached a well-tolerated edema-free state and demonstrated significant improvement in NYHA functional class. Brain natriuretic peptide decreased significantly after 3 months of treatment and remained stable at 6 months. C-reactive protein, a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Systemic pro-inflammatory cytokines is a significant risk factor suggestive of infection in patients with PD (28). However, recently it was reported that circulating pro-inflammatory cytokines TNF-α and IL-6 decreased significantly after 3 months of PD and remained low at 6 months of follow-up in patients with heart failure undergoing PD due to overflow (29). The patients included in the study did not have heart failure, but the information could partially explain the behavior of the pro-inflammatory cytokines in the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic pro-inflammatory cytokines is a significant risk factor suggestive of infection in patients with PD (28). However, recently it was reported that circulating pro-inflammatory cytokines TNF-α and IL-6 decreased significantly after 3 months of PD and remained low at 6 months of follow-up in patients with heart failure undergoing PD due to overflow (29). The patients included in the study did not have heart failure, but the information could partially explain the behavior of the pro-inflammatory cytokines in the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have a molecular weight that ranges from 500 to 30,000 Da, and the peritoneum is permeable to these solutes. Their removal from the blood positively affects the half-life of myocardial cells [55,56]. Moreover, PD may improve the sensitivity to HF treatment.…”
Section: The Role Of Peritoneal Dialysismentioning
confidence: 99%
“…Treatment of systemic congestion is one of the most difficult challenges in the management of severe CHF, particularly in patients with diuretic resistance. Peritoneal dialysis (PD) provides daily fluid removal and has several advantages compared with ultrafiltration through hemodialysis (HD): minimal impact on hemodynamics, slower decline in residual kidney function, sodium sieving with maintenance of normonatremia, possibility of draining of ascites, avoidance of risks related to a vascular access and improvement of systemic inflammatory state 3‐5 . It was demonstrated that in severe CHF patients PD improves functional status and quality of life, reduces hospitalisation rate and may even decrease mortality rate 6‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…avoidance of risks related to a vascular access and improvement of systemic inflammatory state. [3][4][5] It was demonstrated that in severe CHF patients PD improves functional status and quality of life, reduces hospitalisation rate and may even decrease mortality rate. [6][7][8][9] Moreover, PD is associated with a higher risk of insulin resistance, dyslipidemia and metabolic syndrome, while in HD there is better control of sodium and water balance.…”
mentioning
confidence: 99%